SINTESIS KOMPOSIT SELULOSA SERBUK GERGAJI KAYU KAMPER-LIMBAH PLASTIK LDPE (LOW DENSITY POLIETHYLENE) DENGAN REAGEN FENTON SEBAGAI AGEN PENGKOPLING - Nurwendi, Hudi; Simpen, I Nengah; Sutha Negara, I Made (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016, 2016)
This research was on the synthesis of cellulose composites from camphor wood sawdust with LDPE waste (cellulose-LDPE) and Fenton reagent (H 2 O 2 /Fe 2+ ) as the coupling agent. This study was divided into three steps: preparation, variation of LDPE composition and H 2 O 2 concentration, and characterization. Preparation was done with cellulose extraction of sawdust and LDPE plastic waste purification. Variation was performed to determine the effect of compositions of LDPE on composites celullose-LDPE and H 2 O 2 concentration on Fenton reagent. Characterization was done by testing the physical properties and functional groups using FTIR analysis. The best values of the physical property were obtained from cellulose-LDPE composition ratio of 1:5 on 1.5% H 2 O 2 . These were MOE (Modulus of Elasticity) of 12.71 MPa, MOR (Modulus of Rupture) of 200.24 MPa and density of 0.7936 g/cm. FTIR analysis showed the higher the composition of LDPE, the higher the wavenumber for OH and the increase of H 2 O 2 concentration increased the C-H wavenumber functional groups.
Keywords: Composites, Cellulose Sawdust, Plastic LDPE waste, Fenton Reagent